Self-esteem and stress: a structural equation modelling of biosocial determinants, psychological mediators and anxiety among Malaysian undergraduates - Muhammad Ikhwan Mud Shukri; Anisah Baharom; Ahmad Iqmer Nashriq Mohd Nazan (PeerJ, 2025)
Anxiety is a widespread public health concern affecting youth worldwide, leading to significant functional and social disabilities, various negative social and financial consequences, and even suicidality. However, there is a lack of research examining the roles of self-esteem and stress in mediating factors contributing to anxiety among undergraduate students, particularly in Malaysia. Therefore, this research aims to investigate these determinants and the mediating effects of self-esteem and stress on the relationship between biosocial factors and anxiety among Malaysian undergraduates. A cross-sectional study was conducted with 1,193 undergraduates using a validated questionnaire. The study examined independent variables including gender, sleep quality, problematic internet use, social support, and mental health literacy; mediators (self-esteem and stress); and anxiety as the dependent variable. After excluding 68 potential outliers, the final structural equation model demonstrated satisfactory goodness of fit (root mean square error of approximation (RMSEA) = 0.041, χ2/df = 2.918, and comparative fit index (CFI) = 0.925). Mediation analysis using the bootstrapping method revealed that self-esteem and stress fully mediate the relationship between gender, problematic internet use, social support, and anxiety. Mental health literacy was found to be fully mediated by self-esteem alone. Both self-esteem and stress partially mediated the relationship between sleep quality and anxiety. The full mediation structural model accounted for 63.8% of the variance in anxiety. Interventional efforts targeting anxiety among undergraduates could significantly benefit from strategies aimed at enhancing self-esteem and mitigating stress. Future research should explore the levels of emotional social support and its association with anxiety among undergraduate students.